Spectroscopic observation of oxygen dissociation on nitrogen-doped graphene - Mattia Scardamaglia; Toma Susi; Claudia Struzzi; Rony Snyders; Giovanni Di Santo; Luca Petaccia; Carla Bittencourt (Scientific Reports, 2017)
Abstract Carbon nanomaterials’ reactivity towards oxygen is very poor, limiting their potential applications. However, nitrogen doping is an established way to introduce active sites that facilitate interaction with gases. This boosts the materials’ reactivity for bio-/gas sensing and enhances their catalytic performance for the oxygen reduction reaction. Despite this interest, the role of differently bonded nitrogen dopants in the interaction with oxygen is obscured by experimental challenges and has so far resisted clear conclusions. We study the interaction of molecular oxygen with graphene doped via nitrogen plasma by in situ high-resolution synchrotron techniques, supported by density functional theory core level simulations. The interaction leads to oxygen dissociation and the formation of carbon-oxygen single bonds on graphene, along with a band gap opening and a rounding of the Dirac cone. The change of the N 1 s core level signal indicates that graphitic nitrogen is involved in the observed mechanism: the adsorbed oxygen molecule is dissociated and the two O atoms chemisorb with epoxy bonds to the nearest carbon neighbours of the graphitic nitrogen. Our findings help resolve existing controversies and offer compelling new evidence of the ORR pathway.